VD_FINDINFO Décision / 2011 / 286 vom 17. Juni 2011 - VD Tribunal cantonal (2011)
FRAIS JUDICIAIRES, DÉPENS, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ | 61 let. a LPGA, 61 let. g LPGA, 52 LPA-VD, 55 al. 1 LPA-VD, 94 al. 1 let. a LPA-VD